Precisazioni sulla collezione di Giuseppe d'Alessandro di Pescolanciano (1715) e su un inedito Lorenzo De Caro (1760) - Acanfora, Elisa 1960- (2024)
The essay examines the collection of the noble d’Alessandro family, once housed partly in the castle of Pescolanciano (Molise) and partly in the palace in Naples. It presents the unpublished inventory compiled on October 26, 1715, at the death of Duke Giuseppe (1656-1715), patron of the Flemish painter Guglielmo Borremans. As the inventory documents, the works of art collected were made almost exclusively in Naples’ most famous ateliers. Thus, Neapolitan paintings and furniture entered the Pescolanciano castle, making it a model of collecting and furnishing according to the most up-to-date taste of the capital. Among the family’s important commissions, the essay presents an unpublished Decapitation of St. Alexander, painted by Lorenzo De Caro in 1760, probably for Duke Nicola Maria I d’Alessandro (1726-1764).